The Resistance of the Warga Desa Adat to the Reclamation of Benoa Bay, Bali - I Made Anom Wiranata; Kadek Dwita Apriani; Putu Ratih Kumala Dewi (ETNOSIA : Jurnal Etnografi Indonesia, 2026)
Reclamation is not inherently problematic and can yield positive results when well-planned, compliant with environmental standards, and mindful of social impacts. However, many reclamation projects have caused problems and sparked public protest. While most studies on reclamation plan typically examine social movements as a collective entity, this study explores the individual reasons for engagement through the lens of the actors subjective lived experiences in regard to social resistance  against reclamation plan of Benoa Bay. The long movement to reject the plan (2013-2019) depicts the struggle of the Balinese people to uplift their traditional existence in the modern day. Using phenomenological qualitative approach, this study was conducted in Tanjung Benoa Traditional Village. Data collection was based on the narratives produced by series of long and frequent interviews with five main actors of the resistance, consisting of a local fisherman, two youth leaders, a traditional leader, and a hamlet head.  This study indicates that the actors defend their subjective significance of the Benoa Bay in various claims and stories which significantly becomes the driving force of their personal engagement of rejection. The public contest against reclamation was related more to people’s cultural belief and social-environmental solidarity with each other than to political-economic interests.  The Balinese rejection as a whole is not a single movement that is well-organised. The social resistance against the plan of reclamation, in the context of Balinese people, consists of multiple layers of the individual and existential motivations and beliefs. The Balinese beliefs not only sophisticatedly display the local religion, but also the existential struggle of the adat villagers against the onslaught of capitalism that offers modern progress. Myth and modern science are not only competing, but also intertwining. The conceptualisation of the resistance varies in terms of individual engagement.